Early Detection of Breast Cancer According to Fertile Age Women - Okta Sri Rahmayani; Ryan Hara Permana; Witdiawati Witdiawati (Universitas Muhammadiyah Semarang, 2020)
Breast cancer is currently still the leading cause of death in women both in the world and in Indonesia. Fertile age women, a routine of Breast Self-Examination (BSE) can help them detect and prevent mortality from breast cancer. Knowledge is one of the main factors that contribute to the implementation of BSE. This study aims to determine the description of fertile age women’s knowledge regarding the early detection of breast cancer with BSE. This study used a quantitative descriptive design with a population that is the fertile age women in Tegal Panjang Village, Garut. The number of samples is 90 women gained by Cluster Random Sampling with Slovin’s formula. This study used a closed questionnaire consisting of 28 questions. The results showed that most of the fertile age women had a sufficient level of knowledge about early detection of breast cancer. In conclusion, the level of the respondent's knowledge regarding the early detection of breast cancer is still not optimal. This may be influenced by the low level of education and exposure to health education. Optimization of health education and health promotion needs to be done to increase fertile age women’s knowledge about BSE.